2009
DOI: 10.1111/j.1365-2184.2008.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PI3‐k/Akt short hairpin RNA on proliferation, fibronectin production and synthesis of thrombospondin‐1 and transforming growth factor‐β1 in glomerular mesangial cells induced by sublytic C5b‐9 complexes

Abstract: These data indicate that sublytic C5b-9 can promote proliferation of GMCs and secretion of fibronectin as well as synthesis of thrombospondin-1 and transforming growth factor-beta(1). The PI3-k/Akt signal pathway in these reactions, mediated by sublytic C5b-9 complexes, may play at least a partial role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…During the process of Thy-1N induction, GMC undergo apoptosis or proliferation (4,10). The GMC apoptosis in the early phase is considered to be a contributor to the initiation of nephritis (4,11).…”
mentioning
confidence: 99%
“…During the process of Thy-1N induction, GMC undergo apoptosis or proliferation (4,10). The GMC apoptosis in the early phase is considered to be a contributor to the initiation of nephritis (4,11).…”
mentioning
confidence: 99%
“…Our previous microarray analysis detected the up-regulated expression of Gadd45g gene in the renal tissue of Thy-1N rats [20] and in GMC stimulated by sublytic C5b-9 complexes (unpublished data). However, the role of Gadd45g gene in GMC apoptosis of Thy-1N remains to be defined.Given that the injury of GMC in Thy-1N rats is complementdependent and neutrophil-independent [21][22][23][24][25], and that the Gadd45g gene is up-regulated during the development of Thy-1N, we aimed to examine whether the GMC apoptosis in Thy-1N is mediated by sublytic C5b-9 complexes and whether up-regulated Gadd45g gene expression is involved in GMC apoptosis. In addition, we sought to determine whether inhibition of Gadd45g expression can alleviate the pathologic changes such as GMC apoptosis in rats with Thy-1N.…”
mentioning
confidence: 99%
“…34 Our experiments have revealed that sublytic C5b-9 can trigger activation of the PI3-k/Akt signal pathway in GMCs, causing activation of some transcription factors, i.e., early growth response-1 (data not shown), and release of inflammatory mediators (i.e., nitric oxide) or cytokines (i.e., tumor-necrosis factor-a. 10,21 Because ATF3 is a nuclear transcription factor induced by stress signals, 28,35,36 upregulation of ATF3 express- The data analysis showed that the percentage of GMC apoptosis increased significantly at 3 h after sublytic C5b-9 attack compared with other control groups (**P,0.01 vs MEM, gg P,0.01 vs Thy-1 Ab, %% P,0.01 vs Thy-1 Ab1HIS, ## P,0.01 vs Thy-1 Ab1C6DS). All data represent averages and mean6SD from three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…10,21 The different changes in GMC damage may be associated with the dose and time of complement C5b-9 complex stimulation or cell age, and activity and number of homologous restriction factors on the GMC surface. In addition, the fragments of some GMCs that undergo apoptosis may be a stimulus to other undamaged GMCs and lead to the release of inflammatory mediators or cytokines from GMCs or infiltrating macrophage phagocytosis, causing secondary cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation